Nazis on the run : how Hitler's henchmen fled justice - Steinacher, Gerald 1970- (Oxford University Press, 2011)
Steinacher not only reveals how Nazi war criminals escaped from justice at the end of the Second World War, fleeing through the Tyrolean Alps to Italian seaports, but he also highlights the key roles played by the Red Cross, the Vatican, and the Secret Services of the major powers. --from publisher description